Risk management index - Muhammad, Mohd Yusof (2014)
Because of the complex nature, risk and uncertainty are more widespread in construction industry than many other industries. The risk management is an indispensable discipline for any organisation to achieve its objectives. Aiming to ensure that all project objectives are met, risk management is considered as a critical success factor for construction projects. The core components of risk management are now known and utilised by many organizations. Meanwhile, as declared by Project Management Institute (PMI), the ability to measure the effectiveness in managing risk is one of the most vital areas that risk management needs to be developed in. Created to evaluate the capability of a project or an organization in a particular area, a maturity model aids in determining strengths and weaknesses, and to target advance strategies accordingly. Several maturity models have been developed for the area of risk management and furthermore, an attempt to adapt a generic risk management maturity model to the construction industry was specified from the literature. Outstanding risk management maturity models were investigated, six of them were identified as being competent and further examined in terms of their usability and effectiveness. Based on the coparisons and evaluation made among the models, several advantageous and disadvantageous points were inferred. All in all, when examined, it was seen that most of these models outline the topics to be observed in a maturity assessment and provide guidance in terms of content. It was believed that a practical approach was needed and the diagnostic characteristics of these models should be improved.